1995
DOI: 10.4319/lo.1995.40.6.1019
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial secondary production in oxic and anoxic freshwaters

Abstract: Across a series of nine lakes that ranged from ultraoligotrophic to eutrophic, bacterial production was greatest in anoxic hypolimnetic water despite lower hypolimnetic temperatures. Mean (by lake) aerobic bacterial production ranged from 2.6 to 17 mg C rnp3dp 1 while mean anaerobic bacterial production ranged from 1.1 to 47 C mg C rnp3dp I. Overall mean anaerobic bacterial production was 1.6 times greater than mean aerobic bacterial production. The relatively high rates of bacterial production in anoxic water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 35 publications
6
45
1
1
Order By: Relevance
“…The hypolimnion layer shows a positive relation with DOC which is consistent with the results of Maki et al [24]. There is also an inverse relation with pH, related to increasing anoxic bacterial production, which causes pH reduction [25,26]. Variation of temperature and dissolved oxygen from the lake surface to 20 m depth during February 2011.…”
Section: Seasonal Analysissupporting
confidence: 79%
“…The hypolimnion layer shows a positive relation with DOC which is consistent with the results of Maki et al [24]. There is also an inverse relation with pH, related to increasing anoxic bacterial production, which causes pH reduction [25,26]. Variation of temperature and dissolved oxygen from the lake surface to 20 m depth during February 2011.…”
Section: Seasonal Analysissupporting
confidence: 79%
“…Iriberri et al 1985, White et al 1991, Shiah & Ducklow 1994, Sherry et al 1999, no such relationship above 10°C was found by Scavia & Laird (1987) in Lake Michigan or by Cole & Pace (1995) in 9 North American lakes, and none was evident in Lake Kinneret.…”
Section: Bbp and Ppmentioning
confidence: 84%
“…At present we have no explanation for this discrepancy, although the question of the value assigned to the photosynthetic quotient in order to transform O 2 to C in this method is critical. White et al (1991) listed bacterial growth rates ranging from 0.017 to 8.7 d -1 for 10 eutrophic and 14 mesotrophic lakes, and Cole & Pace (1995) reported bacterial specific growth rates from 0.02 to 4.6 d -1 for a variety of freshwater and marine locations. The average bacterial growth rates for photic zone bacteria in Lake Kinneret (0.…”
Section: Cr and Gpp; Net Autotrophy And Net Hetrotrophy In The Phototmentioning
confidence: 99%
“…With seasonally lower hypolimnetic O 2 concentrations, the likelihood of anoxia at the sediment level would increase, with potentially negative consequences to secondary benthic communities. Cole and Pace (1995) show that anoxic conditions lead to higher abundances of sediment bacteria, but a slower doubling time. It is suggested that this could lead to higher rates of organic matter preservation, which would be consistent with our own findings.…”
Section: Benthic Mineralizationmentioning
confidence: 99%